2019
DOI: 10.1016/j.jses.2019.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Delayed hospital discharge after total shoulder arthroplasty: why, and who is at risk?

Abstract: BackgroundThere is growing policy interest in reducing the length of stay (LOS) after discretionary orthopedic surgery but few data to guide improvement efforts. We characterized the primary reasons and predisposing factors associated with extended LOS after elective total shoulder arthroplasty.MethodsWe retrospectively identified 415 patients undergoing elective primary total shoulder arthroplasty between 2016 and 2017. Extended LOS was defined as a stay greater than the 75th percentile. Medical records were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
1
12
2
1
Order By: Relevance
“…Additionally, data on possible readmissions or emergency department visits at other hospitals were not available and may have not been recorded in the patient record. However, the low readmission rates reported in this study are similar to rates reported in past studies 6 , 10 , 20 , 212 , 23 . The rate of anatomic (TSA) and reverse shoulder arthroplasty (RSA) procedures differed between the two groups, with more RSA patients in the post-COVID group.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, data on possible readmissions or emergency department visits at other hospitals were not available and may have not been recorded in the patient record. However, the low readmission rates reported in this study are similar to rates reported in past studies 6 , 10 , 20 , 212 , 23 . The rate of anatomic (TSA) and reverse shoulder arthroplasty (RSA) procedures differed between the two groups, with more RSA patients in the post-COVID group.…”
Section: Discussionsupporting
confidence: 91%
“…The disproportionate number of younger patients in the outpatient group can be explained by the fact that younger patients have less comorbidities and are thus safer for the outpatient pathway. However, the under representation of females in the outpatient groups could be related to surgeon selection bias, as female sex has been reported to be a significant predictor for longer hospitalization [ 30 , 31 ]. Another finding in this review was that the outpatient group was generally healthier than their inpatient counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that baseline preoperative patient characteristics remained unchanged compared to before the outbreak suggests that the observed changes in discharge patterns may indeed be a direct consequence of COVID. There is recent evidence that sociodemographic and psychological factors may have more influence than patient infirmity and technical issues in the variation in LOS and discharge disposition after shoulder arthro-plasty [11]. Although this requires formal investigation, it is possible that patients may be more motivated to go home after surgery during the pandemic to minimize risk of contagion [8].…”
Section: Discussionmentioning
confidence: 99%